Synthesis of a polyacrylonitrile/tetrachloro-1,4-benzoquinone gel polymer electrolyte for high-performance Li-air batteries - Kim, Young Bok; Kim, Il To; Song, Myeong Jun; Shin, Moo Whan (Journal of membrane science, 2018)
Gel polymer electrolyte (GPE) is recently attracting a significant attention for lithium air batteries (LABs) due to better reliability compared with liquid type electrolyte and higher ionic conductivity compared with solid type electrolyte. In this paper, we report a new combination of polyacrylonitrile (PAN)-based GPE with tetrachloro-1,4-benzoquinone (tCl-pBQ) as the redox mediator for the LAB application. The synthesized PAN/tCl-pBQ GPE with lithium bis (tri-fluoro-methane-sulfonyl)imide (LiTFSI)/tetraethylene glycol dimethyl ether (TEGDME) displays a decrease in the LAB charge voltage from ~ 4.2 to 3.6 V and a ~ 10% increase in energy cycle efficiency compared with PAN GPE without tCl-pBQ. The decrease in charge voltage improves the cyclability from 8 to 98 cycles. Structural analyses reveal that addition of tCl-pBQ accelerates the formation of an amorphous phase in the PAN-based gel polymer electrolyte matrix, improving the ionic conductivity from 7.64 to 12.5 mS cm−1 at room temperature. [Display omitted] •The PAN/tCl-pBQ composite GPE synthesized via casting method with electrospinning.•The redox mediator effect of tCl-pBQ was proved by cyclic voltammetry.•Using the PAN/tCl-pBQ GPE shows much improvement of cyclability for Li-air batteries.